2021
DOI: 10.1186/s12902-021-00905-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radioiodine treatment on the characteristics of TRAb in Graves’ disease

Abstract: Background Graves’ disease (GD) is one of the most common autoimmune thyroid diseases (AITDs) in humans, and thyrotropin receptor antibody (TRAb) is a characterized autoantibody in GD. The use of radioactive iodine therapy (RAI) for GD treatment is increasing. Objectives We studied the biological properties of TRAb and evaluated the effect of RAI therapy on TRAb in GD patients. Methods In total, 225 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In our study, we found that the TRAb levels increased 3 months after RIT, and slightly decreased (but not statistically significant) at 6 months, and significantly decreased at 12 months follow-up. The time course changes in TRAb in our study was largely consistent with that of Fang, which showed an increase of TRAb after 6 months and a decline after 12 months’ RAI [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we found that the TRAb levels increased 3 months after RIT, and slightly decreased (but not statistically significant) at 6 months, and significantly decreased at 12 months follow-up. The time course changes in TRAb in our study was largely consistent with that of Fang, which showed an increase of TRAb after 6 months and a decline after 12 months’ RAI [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…In patients with Graves’ hyperthyroidism, TPO Ab status is neither routinely evaluated during the diagnostic workup nor measured to guide management. Treatment with RAI is known to elicit an increase in thyroid antibodies for approximately 1 year, including TPO Ab, considered an immune response secondary to the release of thyroid antigens ( 12 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to this matter, it is important to consider that levels of AbTg may increase or return to positive values within six months after receiving RAI treatment. This phenomenon is predominantly caused by the release of antigens from any remaining thyroid tissue and should not be automatically interpreted as a recurrence of cancer [54][55][56].…”
Section: Discussionmentioning
confidence: 99%